Elaboración de una manual de riesgos mecánicos, mecánica industrial y electricidad, en la Unidad Educativa Siete de Octubre, Quevedo 2017 - Sánchez Quintana, Cynthia Dayana (2017)
This research project was carried out with the objective of elaborating manuals of mechanical and electrical risks for the workshops of automotive mechanics, industrial mechanics and electricity of the Unidad Educativa Siete de Octubre. The risks in which teachers and students were exposed in carrying out the activities were identified and evaluated through the application of the matrix of Identificación y Evaluación de Riesgos of INHST., it was shown that the main risks to which they are exposed are mechanical and electrical, these risks are aggravated due to the omission of the use of personal protective equipment. A compliance matrix was drawn up by reference to Decreto Ejecutivo 2393 and Acuerdo No. 013, where it was determined that the infrastructure of the workshops complies with 55.43% of the evaluated aspects of the regulations and the machines that are used by users comply with 100% of the requirements of current legislation. After carrying out the information gathering, preventive and corrective measures were established that contribute to the good functioning of the workshops which were socialized to the rector of the institution, along with the preparation of manuals of mechanical and electrical risks according to the characteristics of the activities of each workshop, recommendations that contribute to risk control and accident prevention. These manuals were socialized to students and given to each teacher in the areas of Electromecánica Automotriz, Mecanizado y Construcciones Mecánicas y Equipos y Máquinas Eléctricas, who will be responsible for replicating it to their students. Being a great contribution for the security of the users. Keywords: Risk factors, prevention, machines, unsafe acts.